2011
DOI: 10.1074/jbc.m110.198374
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Metastases of Human Lung Cancer Are Inhibited in Mouse Xenografts by a Transition State Analogue of 5′-Methylthioadenosine Phosphorylase

Abstract: The S-adenosylmethionine (AdoMet) salvage enzyme 5 -methylthioadenosine phosphorylase (MTAP) has been implicated as both a cancer target and a tumor suppressor. We tested these hypotheses in mouse xenografts of human lung cancers. AdoMet recycling from 5 -methylthioadenosine (MTA) was blocked by inhibition of MTAP with methylthioDADMe-Immucillin-A (MTDIA), an orally available, nontoxic, picomolar transition state analogue. Blood, urine, and tumor levels of MTA increased in response to MTDIA treatment. Disrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(118 citation statements)
references
References 34 publications
(37 reference statements)
7
110
0
1
Order By: Relevance
“…MTA, through the action of 5'-deoxy-5'-methylthioadenosine phosphorylase (MTAP), is involved in S-adenosylmethionine (AdoMet) salvage, purine salvage and spermidine synthesis (40). MTAP activity has been shown to be reduced in a wide variety of tumor types including NSCLC (41).…”
Section: Discussionmentioning
confidence: 99%
“…MTA, through the action of 5'-deoxy-5'-methylthioadenosine phosphorylase (MTAP), is involved in S-adenosylmethionine (AdoMet) salvage, purine salvage and spermidine synthesis (40). MTAP activity has been shown to be reduced in a wide variety of tumor types including NSCLC (41).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a loss of MTAP expression sensitizes cancer cells to DNSP inhibitors, as shown in studies on leukemia and lung cell lines [30] and various malignant neoplasms [27] . This is particularly relevant for lymphomas, leukemias [27,29] and nonsmall-cell lung carcinoma [34,45] . Nevertheless, chemotherapy regimens with pemetrexed were not effective for pediatric patients with medulloblastomas, ependymomas and high-grade gliomas [49] , and the addition of methotrexate in the chemotherapeutic treatment of infratentorial ependymomas did not improve the response to these drugs [50] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MTAP deletion increases the sensitivity of neoplastic cells to DNSP inhibitors such as methotrexate, L -alanosine and pemetrexed [27,30] , particularly in leukemia [29,30] and other solid tumors, e.g. in the lung, liver and breast [30,[33][34][35] . In tumors of the central nervous system, deletion and gene copy-number breakpoints of MTAP have been reported in glioblastomas [36,37] , and in pediatric high-grade gliomas [38] , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, where whole-body methylthioadenosine phosphorylase (MTAP) is blocked by MTDIA, 24 dramatic effects are observed in mouse xenografts of a variety of human tumours. 25,26 Also, MTDIA is a femtomolar inhibitor of the dual-substrate enzyme methylthioadenosine/S-adenosylhomocysteine nucleosidase (MTAN) 27 from E. coli and MTDIA and its analogues may act as antibiotics that do not induce resistance. 28,29 …”
Section: Introductionmentioning
confidence: 99%